2020
DOI: 10.1002/hep4.1609
|View full text |Cite
|
Sign up to set email alerts
|

High‐Fat Diet Modulates Hepatic Amyloid β and Cerebrosterol Metabolism in the Triple Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Long‐term high‐fat diet–induced changes in liver function impact peripheral AD features and should be considered during development of biomarkers or therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…It fully develops neuropathological and behavioral changes around 12 months of age (Arsenault et al, 2013;Belfiore et al, 2019;Dal-Pan et al, 2017;Vandal et al, 2015;Vandal et al, 2016). Previous studies showed that 3xTg-AD mice also display metabolic disorders (Bosoi et al, 2021;Julien et al, 2010;Nicholson et al, 2010;Sanguinetti et al, 2019;Vandal et al, 2015;Vandal et al, 2014;Velazquez et al, 2017), and their brain Aβ concentrations quickly decrease after insulin administration (Chen et al, 2014;Vandal et al, 2014). Here, they were compared with non transgenic (Non-Tg) littermates with the same genetic background (C57Bl6/129SvJ).…”
Section: Animalsmentioning
confidence: 98%
“…It fully develops neuropathological and behavioral changes around 12 months of age (Arsenault et al, 2013;Belfiore et al, 2019;Dal-Pan et al, 2017;Vandal et al, 2015;Vandal et al, 2016). Previous studies showed that 3xTg-AD mice also display metabolic disorders (Bosoi et al, 2021;Julien et al, 2010;Nicholson et al, 2010;Sanguinetti et al, 2019;Vandal et al, 2015;Vandal et al, 2014;Velazquez et al, 2017), and their brain Aβ concentrations quickly decrease after insulin administration (Chen et al, 2014;Vandal et al, 2014). Here, they were compared with non transgenic (Non-Tg) littermates with the same genetic background (C57Bl6/129SvJ).…”
Section: Animalsmentioning
confidence: 98%
“…Indeed, the possibility of formatting triglyceride-rich lipoprotein-A β complexes and their extravasation may lead to cerebral capillary amyloid angiopathies ( Matsubara et al, 2004 ). Thus, the number of circulating triglycerides and cholesterol is correlated with A β levels rather than other liver markers such as transaminases ( Bosoi et al, 2021 ). Amyloidosis is also accelerated in atherogenic diets in an animal model of pre-symptomatic AD consisting of amyloid precursor protein/presenilin 1 (APP/PS1) mice.…”
Section: Disrupted Amyloid Beta (A β ) Metabolism ...mentioning
confidence: 99%
“…Regarding AD, Bossio and others recently demonstrated that a high-fat diet (HFD) modulates hepatic A β and cerebrosterol metabolism using a triple transgenic mouse model of AD ( Bosoi et al, 2021 ). Cerebrosterol is the principal way of eliminating brain cholesterol and once produced in brain, the liver is the main organ responsible for cerebrosterol glucuronidation or sulfation by eliminating it through bile acids and urine ( Björkhem, 2006 ).…”
Section: Disrupted Amyloid Beta (A β ) Metabolism ...mentioning
confidence: 99%
“…In addition to liver injury, NAFLD has been associated with neurological pathologies, including decreased cognitive function [ 1 , 3 , 4 , 5 ], and smaller brain volume [ 4 , 6 ]. Further evidence of a link between liver and brain disorders is shown by the development of neuropathological hallmarks of Alzheimer’s disease (AD) in rodent and pig models of NASH [ 7 , 8 , 9 ] and the presence of altered hepatic markers in patients with AD [ 10 , 11 ]. A liver–brain axis of neurodegeneration has been established through common risk factors, such as obesity, type 2 diabetes, and high-fat diets [ 7 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence of a link between liver and brain disorders is shown by the development of neuropathological hallmarks of Alzheimer’s disease (AD) in rodent and pig models of NASH [ 7 , 8 , 9 ] and the presence of altered hepatic markers in patients with AD [ 10 , 11 ]. A liver–brain axis of neurodegeneration has been established through common risk factors, such as obesity, type 2 diabetes, and high-fat diets [ 7 , 12 , 13 , 14 ]. In this regard, recent clinical and translational studies have shown an effect of dietary interventions on brain function, such as changes in cognitive processes, memory and learning, motor function, neuroinflammation, synaptic transmission, and neurotransmitter pathways [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%